Situation of Binge Drinking Among the Rural Adults Living at Thailand's Border of Shan State, Myanmar - Sai Hline Pan; Kavin Thinkhamrop (International Journal of Public Health Asia Pacific, 2026)
Background: Binge drinking is a pattern of excessive alcohol consumption where men consume five or more drinks, and women consume four or more drinks, within two hours. Binge drinking is associated with short-term and long-term health consequences, including mental health problems. Objectives: This study aimed to assess the prevalence and factors associated with binge drinking in Thailand-Shan state border area of Myanmar. Methods: A cross-sectional study using a structured questionnaire was conducted on 460 individuals living in remote villages of Langkho Township, Shan State, Myanmar, from November 2024 to May 2025. Multiple logistic regression was performed to examine the association between binge drinking and sociodemographic characteristics, physical and mental health conditions, behavioural factors, and environmental influences. Adjusted odds ratios (AORs) with 95% confidence intervals (95% CIs) were reported, with a statistically significant alpha at a P-value of < 0.05. Results: Among the 460 participants, the overall prevalence of binge drinking was 24.35% (95% CI: 20.63-28.49), with the highest prevalence observed among males (39.11%, 95% CI: 32.92-45.67). Factors significantly associated with increased odds of binge drinking included current smoking (AOR = 5.16; 95% CI: 2.99-8.90), having a family member who drinks alcohol (AOR = 1.66; 95% CI: 1.02-2.70) and having a friend who drinks alcohol (AOR = 3.89; 95% CI: 2.06-7.33). Conclusion: Binge drinking is prevalent among the population along Thailand’s border of Shan State, Myanmar, influenced by tobacco use, and environmental influences. Community-based, culturally sensitive interventions addressing these determinants are essential to reduce the prevalence of binge drinking and its associated harms.